CASE STUDY ON DECISION MAKING AT VIBRANT PAINTS- IS IT RATIONAL? - Srinivas, Mr. V S M; R. Anita; Dr. Veenapani; Sharma, Dr. Monali (The journal of contemporary issues in business and government, 2022)
The case represents a company named Vibrant Paints who faced a huge loss because of a decision taken by the accounts manager to stop paying transit insurance. It tells about the incident that a company faced and they suffered losses for several years. One evening Akhil was sitting in his office and was just thinking about the sequence of incidents that had happened a few months ago. He was trying to understand the impact of the decision about transit insurance on the reputation of the company. He was planning to meet his friend Sonu who is the marketing manager to understand the sales growth of the products sold. Just then he got a call from the CEO of the company to meet him.